Assessment of serum Vit A, D and zinc nutritional status and related dietary and exercise behaviors of children and adolescents in rural and urban area - Zou, Yan; Huang, Li-chun; Zhao, Dong; He, Meng-jie; Su, Danting; Zhang, Rong-hua (Frontiers in Nutrition, 2023)
Vitamin A and vitamin D deficiency in children and adolescents has a negative impact on their growth and development. This study aimed to learn the nutritional status of vitamin A and D among rural children and adolescents and to explore related dietary and exercise behaviors. A total of 10 counties (cities, districts) from 90 counties (cities, districts) in Zhejiang Province were selected by the method of random cluster sampling. Children and adolescents were investigated and their food and nutrient intake were calculated. The concentration of serum vitamin A in urban area was 0.38ng/ml, which was higher than that in rural area（p<0.05）; while the concentration of serum vitamin D in urban area was 21.25mg/L，which was lower than that in rural area(p<0.05). The concentration of serum zinc was 101 μg/dl in urban area and 107 μg/dl in rural area(p<0.05). The intake of dietary fiber, calcium, vitamin A, vitamin B1, vitamin B2 and vitamin C was lower than the recommended value. In rural area, the intakes of cereals, tubers and beans, livestock, poultry and meat of children and adolescents in rural area were higher than the recommended values; while the intake of vegetables, fruits, eggs, milk, fish and shrimp, soybean and nuts was lower than the recommended value. The intake of edible oil and salt is higher than the recommended value. The time of high-intensity exercise in rural area is more than that in urban are in the age group of 12-17 , while the sitting time is less than that in cities. Children and adolescents living in rural area should be guided to eat reasonably, and choose foods with high nutrient density and with low oil, salt and sugar.